Studies on effect of antioxidants on cattle and buffalo semen during storage at refrigeration temperature - KUMAR, DEVENDRA; DABAS, Y P S; BARDHAN, D (The Indian Journal of Animal Reproduction, 2023)
Effects of antioxidants, viz. butylated hydroxy anisole, Vitamin E, Vitamin C and n-Propyl gallate on physico-morphological characters of semen of Jersey, Holstein Friesian (HF) and Murrah bulls during storage at refrigeration temperature werestudied. It was observed that semen of Jersey, HF and Murrah bulls had better preservability after addition of antioxidants in the diluents. It was further revealed that progressive sperm motility and live sperm percentage were maximum in n-Propyl gallate fortified diluents as compared to other antioxidants' fortified diluents. Butylated hydroxy anisole did -not exhibit positive role for the improvement of progressive sperm motility and live sperm percentage, whereas, it had beneficial effects on acrosomal integrity. Addition of optimum concentration of antioxidants in diluents could be effective to improve semen preservability by preventing lipid peroxidation in sperm cell membrane and thus, its fertility.
Keywords: Cattle; buffalo; antioxidant; semen